Residential Segregation in Israel, 1961-2008. - Keidar, Noga (Israel Studies Review)
While scholars study residential segregation dynamics in order to understand minorities' assimilation into mainstream society, less is known about these mechanisms in ethno-national migration contexts. This article examines Israel's demographic dynamics from 1961 to 2008 in order to evaluate and provide a framework for the process of spatial assimilation of Mizrahim and Ashkenazim in the context of segregation from the Palestinian citizens of Israel. By using the Theil index (H), I assess the level of segregation in different geographic layers and then explore how internal migration has reduced spatial distance within the Jewish society. The analysis demonstrates that despite the disadvantaged position of Mizrahim as of 1961, levels of residential segregation had decreased by 1983. Also, boundaries changed from a variance between Mizrahim and Ashkenazim into a variance among Mizrahim only, with those who relocated as the most spatially assimilated group and those who remained as the most segregated one.